Literary sisters : Dorothy West and her circle : a biography of the Harlem Renaissance - Mitchell, Verner D., 1957-; Davis, Cynthia, 1946- (New Brunswick, N.J. : Rutgers University Press, 2012)
"Harlem Renaissance writer Dorothy West led a charmed life in many respects. Born into a distinguished Boston family, she appeared in Gershwin's Porgy and Bess, then lived in the Soviet Union with a group that included Langston Hughes, to whom she proposed marriage. She later became friends with Jacqueline Kennedy Onassis, who encouraged her to finish her second novel, The Wedding, which became the octogenarian author's first bestseller. Literary Sisters reveals a different side of West's personal and professional lives - her struggles for recognition outside of the traditional literary establishment, and her collaborations with talented African American women writers, artists, and performers who faced these same problems. West and her "literary sisters"--Women like Zora Neale Hurston and West's cousin, poet Helene Johnson - created an emotional support network that also aided in promoting, publishing, and performing their respective works. Integrating rare photos, letters, and archival materials from West's life, Literary Sisters is not only a groundbreaking biography of an increasingly important author but also a vivid portrait of a pivotal moment for African American women in the arts."--Project Muse.
Chapter 1 -- "Nothing So Broadening as Travel"; Chapter 2 -- The Benson Family Comes to Boston; Chapter 3 -- Pauline Hopkins and African American Literature in New England; Chapter 4 -- Boston Girlhoods, 1910-1925; Chapter 5 -- The Youngest Members of the Harlem Renaissance, 1926-1931; Chapter 6 -- Russian Interlude, Literary Salons, and Challenge.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: West, Dorothy, -- 1907-1998 -- Criticism and interpretation; West, Dorothy, -- 1907-1998; American literature -- African American authors -- History and criticism; American literature -- Women authors -- History and criticism; African American women -- Intellectual life; African American women in literature; Harlem (New York, N.Y.) -- Intellectual life -- 20th century; African American arts -- New York (State) -- New York; Harlem Renaissance; Écrits de femmes américains -- Histoire et critique; Noires américaines -- Vie intellectuelle; Arts noirs américains -- New York (État) -- New York; Harlem Renaissance; Harlem Renaissance; LITERARY CRITICISM -- American -- General; SOCIAL SCIENCE -- Women's Studies; African American arts; African American women in literature; African American women -- Intellectual life; American literature -- African American authors; American literature -- Women authors; Harlem Renaissance; Intellectual life; New York (State) -- New York; New York (State) -- New York -- Harlem; 1900-1999; Criticism, interpretation, etc